Acute leukemias in a Background of Neurocutaneous Syndromes - Roy, Shipla; Baul, Shuvraneel; Dolai, Tuphan Kanti; Ghosh, Kaustav (Asian Pacific Journal of Cancer Care, 2025)
Background: Neurocutaneous syndromes are a group of hereditary disorders affecting the skin and the central nervous system. The association between neurocutaneous syndromes and acute leukemias is rare, and very few cases have been described in the literature. Methods: Here we present three cases: two cases of acute lymphoblastic leukemia associated with sturge-weber syndrome and one case of acute myeloid leukemia in a known case of tuberous sclerosis. Results: The association between NCS and acute leukemia denotes a poor prognosis, as evident by the fact that two out of three patients in the present triology series expired. Conclusions: One should have a high index of suspicion for malignancies in cancer-predisposing syndromes to help in early diagnosis and treatment. Drugs affecting the mTOR pathway could be of possible benefit to these group of patients along with prophylactic anticonvulsant therapy for seizure prevention.